2020
DOI: 10.1177/0269094220957977
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the role of universities in a place-based Industrial Strategy: Evidence from the UK

Abstract: The UK Government’s Industrial Strategy White Paper, published in November 2017, focuses on several key technologies of the future, in order to promote innovation and future economic performance. Universities play a key role in the delivery of the strategy, marking the culmination of nearly two decades of policy reviews that have continually promoted ‘third stream’ activities of commercial engagement with industry. Given the spatial focus of the strategy, this paper seeks to assess the regional distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
3
0
2
Order By: Relevance
“…Interaction with subjects of the innovation environment. The industrial strategy of the UK emphasizes the key role of the interaction of universities with industrial enterprises (Johnston & Wells, 2020). The expediency of cooperation with universities is confirmed by studies that have shown a more developed ability of university business incubators to create innovations of global novelty compared to technology incubators, which tend to create local innovations (Goraczkowska, 2020).…”
Section: Theoretical Foundations Of the Relationship Between Industrial Growth And Innovative Developmentmentioning
confidence: 98%
“…Interaction with subjects of the innovation environment. The industrial strategy of the UK emphasizes the key role of the interaction of universities with industrial enterprises (Johnston & Wells, 2020). The expediency of cooperation with universities is confirmed by studies that have shown a more developed ability of university business incubators to create innovations of global novelty compared to technology incubators, which tend to create local innovations (Goraczkowska, 2020).…”
Section: Theoretical Foundations Of the Relationship Between Industrial Growth And Innovative Developmentmentioning
confidence: 98%
“…Rajendra Mishra School of Engineering Entrepreneurship, IIT Kharagpur, West Bengal 721302, India Institute of Service Science, National Tsing Hua University, Hsinchu 300044, Taiwan Department of Design, Indian Institute of Technology, Roorkee, Uttarakhand, India В последние годы стратегия производства и использования знаний для стимулирования социальноэкономического развития (третья миссия университетов) приобретает высокую актуальность, обретая новые смыслы для ключевых стейкхолдеров -образовательного, научного и делового сообществ, государственного сектора (Johnston, Wells, 2020). Большинство исследований в этом направлении выполнены на материале развитых стран, в которых вузы выступают одними из ключевых генераторов знаний и инноваций (Benneworth et al, 2009;Trippl et al, 2015;Acosta et al, 2016;Martin, Trippl, 2017).…”
Section: Bhaskar Bhowmickunclassified
“…-повышение доли высококвалифицированных кадров с высшим образованием, рост вклада высокотехнологичных отраслей, увеличение выпуска инновационной продукции, рост масштаба производства и интеграционных процессов, повышение экологичности производств (Макарова, Коровин, 2014); -создание дополнительных рабочих мест, защиту окружающей среды за счет эффективного использования невозобновляемых ресурсов и, в конечном счете, повышение конкурентоспособности экономики (Ulbrych, 2020); -развитие цифровых навыков рабочей силы (Habanik et al, 2019); -коммерческое взаимодействие университетов с промышленными предприятиями (Johnston, Wells, 2020);…”
Section: теорияunclassified